2016
DOI: 10.1016/j.bbacli.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan measured from synovial fluid serves as a useful indicator for progression of Osteoarthritis and complements Kellgren–Lawrence Score

Abstract: BackgroundPlain radiography is the first choice for diagnosis and monitoring of knee-osteoarthritis (OA) while, Kellgren–Lawrence score (KL) is most widely used to grade OA severity. However, incompetency for reproducibility of joint space measurement in longitudinal assessment and non-linearity of KL-score system, limits radiography-based early diagnosis of the disease. Glycosaminoglycan (GAG) is direct cartilage-degradation product, which can be measured biochemically. We strived to correlate KL-score and GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…We also evaluated concentrations of glycosaminoglycans (GAG) in synovial fluid by a spectrophotometric dye binding assay using 1,2, dimethylmethylene blue (DMMB; Santa Cruz Biotechnology) 46 . A positive correlation between GAG concentration in synovial fluid and KL grade was demonstrated in a previous report 28 .…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…We also evaluated concentrations of glycosaminoglycans (GAG) in synovial fluid by a spectrophotometric dye binding assay using 1,2, dimethylmethylene blue (DMMB; Santa Cruz Biotechnology) 46 . A positive correlation between GAG concentration in synovial fluid and KL grade was demonstrated in a previous report 28 .…”
Section: Methodssupporting
confidence: 63%
“…We first confirmed that glycosaminoglycans (GAG), which are degradation products of GAG chains in cartilage proteoglycans 28 , were increased in synovial fluid with increasing OA severities that was evaluated by the Kellgren-Lawrence (KL) radiographic grading system 29 (Fig. 1A–C).…”
Section: Resultsmentioning
confidence: 65%
“…This improvement was also suggested by the lower concentration of GAGs in the synovial fluid of the intervention group joints. Indeed, a higher concentration of GAGs in synovial fluid indicates a release of GAGs from diseased articular cartilage into the synovial fluid, as is seen in naturally occurring OA [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Though, since gagCEST is temperature and pH dependent this would not have been a good choice in these ex vivo studies because those parameters are hard to keep controlled over various samples. 97 . This could be an important factor in the lack of correlation in our DMMB analyses versus sodium concentration, since mostly end-stage OA cartilage has been included.…”
Section: Discussionmentioning
confidence: 99%
“…When scraping off cartilage samples one easily includes some bone or parts of the calcified layer, increasing the overall weight of the sample but decreasing the (relative) amount of GAGs -spoiling the results with a too low GAG measurement. Additionally, at least in synovial fluid, DMMB analyses in end-stage OA seem to have two distinct categories: one with very high GAG content (possible active cartilage degeneration process) and one with very low GAG content (completely worn-out cartilage) 97 . These two causes could be the underlying factors of the lack of correlation of DMMB assays in the lateral condyle in chapter 6 or the samples used in chapter 3.…”
Section: Validationmentioning
confidence: 99%